Health Literacy Overview of Sriwijaya University Students - Bayu, Wahyu Indra; Syafaruddin, Syafaruddin; Syamsuramel, Syamsuramel; Solahuddin, Soleh; Fitri, Arfa Desa; Mukarrobin, Ahmad; Mikail, Ibrahim (Department of Physical Education, Sport, Health and Recreation, 2021)
Covid-19 pandemic has caused behavioral changes in accessing information related to various health information. Previous studies show that the physical literacy of young adult university students is still inadequate. This study aims to describe the health literacy overview of Sriwijaya University students during the Covid-19 pandemic. A total of 764 (M= 191; F= 573) and 17-34 year’s old (19,22; ±1,76) students were participated in this study. This study used a cross-sectional survey using the HLS-SQ10-IDN comprehensive health literacy questionnaire consists of 10 items measuring health literacy. The results show that the health literacy level of Sriwijaya University students during the Covid-19 pandemic was good. The students could easily find information related to health, find out what medical action to take in the case of an emergency, and were aware of health threats. This study is limited to the general health literacy overview of Sriwijaya University students, future studies are suggested to examine several factors that may influence or associate with the health literacy of university students.